SS316/CCA laminated metal composite fabricated by additive friction stir deposition: Microstructure and mechanical properties - Ravi Sankar Haridas; Anurag Gumaste; Eric Kusterer; Devin Davis; Supreeth Gaddam; Brandon McWilliams; Kyu C. Cho; Rajiv S. Mishra (Journal of Materials Research and Technology)
Laminated metal composites (LMCs) are a unique class of metallic composites that contain layers of different alloys that are alternately fabricated, and whose distinct interface characteristics enhance their properties. Conventionally, adhesive bonding, roll bonding or deposition methods are used to engineer the LMC for property optimization. For the first time, the present study investigated the potential of the novel solid-state additive friction stir deposition (AFSD) technique to additively manufacture an LMC containing SS316 and Fe40Co20Mn20Cr15Si5 complex concentrated alloy (CS-CCA) exhibiting transformation induced plasticity (TRIP). The stability of SS316/HEA dissimilar interfaces in the LMC ensured displacement continuity and promoted synchronous deformation of both alloys under tension, which enabled mechanical property enhancement. The study revealed the unprecedented ability of CS-CCA layers in the LMC to sustain ∼50% more transverse strain than their monolithic counterparts. Additionally, the LMC exhibited better strength, work hardening, and failure strain compared to the corresponding weaker counterpart in the LMC. Better work hardening and strength achieved in the LMC were correlated with the unique deformation mechanisms such as TRIP and deformation twinning that prevailed in the TRIP-CCA during tensile deformation, as supported by detailed mechanical and microstructural characterization. The current study provides insights into considering AFSD as an alternate route to roll/press bonding for LMC fabrication of high-strength structural alloys.